A porous composite material based on graphene oxide and porous plant powder, and preparation method and application thereof
By combining porous natural light wood chip powder with graphene oxide, and following specific treatment and high temperature carbonization, a porous composite material with excellent compression performance and self-response ability is prepared, which solves the problem of insufficient toughness of graphene-based porous materials. It also achieves efficient absorption of harmful substances in the flue gas.
Patent Information
- Application Number
- CN202111640904.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-12-29
AI Technical Summary
The toughness of graphene-based porous materials is not sufficient to withstand the large compression deformation and collapse and fracture during the extrusion process, and existing cellulose aerogels cannot fully utilize their unique properties.
By placing porous natural light wood chip powder in a mixed hydrogen peroxide/phosphoric acid solution containing adenine for soaking treatment, cellulose is obtained, then mixed with an aqueous graphene oxide solution, prefreezing and vacuum freeze-drying, and finally high-temperature carbonization is carried out , a porous composite material based on graphene oxide and porous plant powder was prepared.
The prepared porous composite materials have very low density, good compression performance and self-recovery, and have a certain hydrophilicity and can be used to absorb harmful substances in flue gas.
Smart Images

Figure CN116408045B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a porous composite material based on graphene oxide and porous plant powder, a preparation method and application thereof, and belongs to the technical field of composite materials and preparation thereof. Background Art
[0002] Graphene has excellent mechanical properties and is considered to be a revolutionary material of the future. Therefore, graphene composite materials can combine the advantages of all aspects and have research and development potential. Graphene is a porous carbon material with a large specific surface area. It can be assembled into different spatial configurations through regulation, so that it can be used in a variety of fields. Graphene-based composite materials have a strong ability to adsorb harmful substances. However, the toughness of graphene-based porous materials is often not enough to withstand large compression deformation, collapse and fracture during extrusion. Therefore, it is very important to improve the compression performance of materials while ensuring adsorption capacity for the application and development of adsorption materials.
[0003] Cellulose is a natural polymer material widely found in nature. Cellulose aerogel has the advantages of environmental protection and renewability, as well as porous structure characteristics. Due to its excellent biocompatibility and degradability, it is extremely useful in many fields. Although the application development prospects are broad, simple cellulose aerogel cannot give full play to its unique properties. Summary of the invention
[0004] In view of the above problems, the object of the present invention is to provide a porous composite material based on graphene oxide and porous plant powder, and a preparation method and application thereof.
[0005] In a first aspect, the present invention provides a method for preparing a porous composite material based on graphene oxide and porous plant powder, comprising:
[0006] (1) porous natural balsa wood sawdust powder is selected and immersed in a hydrogen peroxide / phosphoric acid mixed solution containing adenine, and then washed and dried to obtain cellulose;
[0007] (2) mixing the graphene oxide aqueous solution and cellulose, and obtaining a composite aerogel by pre-freezing and vacuum freeze-drying;
[0008] (3) The obtained composite aerogel is carbonized at high temperature to obtain a porous composite material based on graphene oxide and porous plant powder.
[0009] In the present invention, natural balsa wood sawdust powder is selected, and cellulose is obtained after being processed and then uniformly mixed with graphene oxide, and mixed aerogel is obtained by precooling in liquid nitrogen and freeze drying, and then carbonized at high temperature to obtain a porous composite material of graphene oxide / sawdust. The porous composite material prepared by the method has a very low density, good compression performance and self-recovery, and has a certain hydrophilicity and hydrophobicity, and can be used to absorb harmful substances in flue gas. This method is simple to operate, has good reproducibility, and has broad application prospects. Specifically, the present invention adds porous natural sawdust powder to the hydrogen peroxide / phosphoric acid mixed solution containing adenine, with the purpose of introducing P and N elements to generate a double heteroatom porous composite material. Among them, H2O2 is to decompose sawdust to prepare cellulose, adenine provides N elements, and phosphoric acid provides P elements. Moreover, the invention selects graphene oxide for compounding. Since hydroxyl, carboxyl and carbon oxygen functional groups are attached to the surface of graphene oxide, it has good hydrophilicity and will have a good selective effect on conjugated molecules, bases, pyrrolidone and ketone molecules.
[0010] Preferably, the particle size of the porous natural balsa wood sawdust powder is ≤6mm; the porous natural balsa wood slices with a longitudinal thickness of ≤3mm are crushed to obtain the porous natural balsa wood sawdust powder; the material of the porous natural balsa wood sawdust powder is at least one of balsa wood, arbor, paulownia wood and catalpa wood.
[0011] Preferably, the hydrogen peroxide / phosphoric acid mixed solution containing adenine comprises: 50-150 mL of a 30 wt % hydrogen peroxide solution, 50-150 mL of a 85.0 wt % phosphoric acid solution, and 15 g-25 g of adenine, which are mixed together.
[0012] Preferably, the soaking treatment temperature is 60-100° C., and the soaking time is 6-10 hours.
[0013] Preferably, the cleaning is performed by soaking in deionized water for several times to remove dissolved chemicals.
[0014] Preferably, the drying temperature is 60-120° C. and the drying time is 6-12 hours.
[0015] Preferably, the mass ratio of cellulose to graphene oxide is 10:(1-6).
[0016] Preferably, the pre-freezing is to freeze and crystallize the mixed solution to a solid state; preferably, the pre-freezing temperature is ≤-10°C, and the pre-freezing time is ≥3 hours.
[0017] Preferably, the vacuum freeze drying temperature is -60 to -80°C, the time is 6 to 10 hours, and the vacuum degree is 1 to 10 Pa.
[0018] Preferably, the high temperature carbonization is: firstly heating to 400-600°C and keeping it for 1-3 hours, then heating to 800-1000°C and keeping it for 1-3 hours; the atmosphere of the high temperature carbonization is an inert atmosphere.
[0019] In a second aspect, the present invention provides a porous composite material based on graphene oxide and porous plant powder prepared according to the above-mentioned preparation method, wherein the porous composite material based on graphene oxide and porous plant powder is composed of neatly arranged fine pore walls, and the gaps between adjacent pores are a multi-channel structure with continuous guidance.
[0020] Preferably, the average pore size of the porous composite material based on graphene oxide and porous plant powder is 300nm to 700nm;
[0021] Preferably, the specific surface area of the porous composite material based on graphene oxide and porous plant powder is 60 to 550 m 2 / g, more preferably 400 to 450 m 2 g -1 ;
[0022] Preferably, the porous composite material based on graphene oxide and porous plant powder can rebound to its original shape after being compressed to 20-80% of its volume;
[0023] Preferably, the hydrophilic angle of the porous composite material based on graphene oxide and porous plant powder is 0 to 40°.
[0024] In a third aspect, the present invention provides an application of a porous composite material based on graphene oxide and porous plant powder in a tobacco filter.
[0025] Beneficial effects:
[0026] In the present invention, the porous composite material based on graphene oxide and porous plant powder has very low density, good compression performance and self-recovery, and has certain hydrophilicity and hydrophobicity, and can be used to absorb harmful substances in flue gas. This method is simple to operate, has good reproducibility, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM image of the porous composite material based on graphene oxide and porous plant powder prepared in Example 2. It can be seen from the image that the modified composite material presents a tubular structure;
[0028] Figure 2 This is the XRD diagram of the porous composite material based on graphene oxide and porous plant powder prepared in Example 2. It can be seen from the figure that the composite material has no other impurity peaks. DETAILED DESCRIPTION
[0029] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0030] In the present invention, the porous composite material based on graphene oxide and porous natural plant powder is composed of neatly arranged fine pore walls, and the gaps between adjacent pores are a multi-channel structure with continuous guidance. The obtained graphene oxide / plant powder composite material has a hydrophilic and hydrophobic porous structure and can be used in tobacco filters to absorb harmful substances in smoke.
[0031] The raw materials of the porous composite material based on graphene oxide and porous natural plant powder in the present invention are locally sourced, the preparation industrial process is simple, and it complies with the environmentally friendly design concept.
[0032] The following is an exemplary description of a method for preparing a porous composite material based on graphene oxide and porous natural plant powder.
[0033] The cellulose is obtained by soaking the natural porous balsa wood sawdust powder. The mixed solution used for soaking is a mixture containing adenine (C 5 H 5 N 5 ,99%) of hydrogen peroxide (H 2 O 2 , 30%) and phosphoric acid (H 3 PO 4 ,≥85.0%) mixed solution. The mixed solution used for soaking contains 50-150 mL of hydrogen peroxide, 50-150 mL of phosphoric acid solution and 15-25 g of adenine. The soaking can be maintained at 60-100° C. for 6-10 hours. Preferably, after the soaking treatment, the mixture is soaked in deionized water for several times (e.g., 3-5 times) to remove dissolved chemicals.
[0034] In an optional embodiment, porous natural balsa wood chips with a typical thickness of 2-6 mm (preferably 3 mm) in the longitudinal direction are crushed to form natural porous balsa wood chip powder.
[0035] After the graphene oxide aqueous solution (for example, 1-6 mg / mL) is uniformly mixed with cellulose, it is pre-frozen and vacuum-dried to obtain a composite aerogel of graphene oxide and cellulose. Alternatively, the graphene oxide aqueous solution and the cellulose aqueous solution are uniformly mixed, pre-frozen with liquid nitrogen, and freeze-dried to obtain a composite aerogel of graphene oxide and cellulose. Wherein, the pre-freezing is to freeze and crystallize the mixed solution to a solid state; preferably, the pre-freezing temperature is ≤-10°C, and the pre-freezing time is ≥3h (for example, the liquid nitrogen pre-freezing is not less than 3h). The temperature of vacuum freeze drying is -50 to -80°C, the time is 6-12 hours, and the vacuum degree can be 1 to 10Pa. Preferably, the temperature of vacuum freeze drying can be -60 to -80°C, the time can be 6-10 hours, and the vacuum degree can be 1 to 3Pa
[0036] The graphene oxide and cellulose composite aerogel are carbonized at high temperature to obtain a porous composite material. As an example of high temperature carbonization, the sample is heated to 400-600°C at a heating rate of 1-5°C / min (e.g., 3°C / min) under an inert atmosphere (e.g., nitrogen, argon, or helium, etc.) and kept warm for 1-3 hours, and then the sample is heated to 800-1000°C at 1-10°C / min (e.g., 5°C / min) and kept warm for 1-3 hours to complete the high temperature carbonization.
[0037] In the present invention, the average pore size of the porous composite material based on graphene oxide and porous plant powder obtained by BET test is 300nm-700nm. The specific surface area of the porous composite material based on graphene oxide and porous plant powder obtained by BET test is 60-550m 2 / g; the porous composite material based on graphene oxide and porous plant powder can rebound to its original volume after being compressed by 20-80% of its volume, and has good compression performance and self-recovery. The hydrophilicity and hydrophobicity of the porous composite material based on graphene oxide and porous plant powder are obtained by using a BET hydrophilicity tester.
[0038] In the present invention, the porous composite material based on graphene oxide and porous plant powder has hydrophilicity and hydrophobicity, and can be used in tobacco filter tips to absorb harmful substances in smoke.
[0039] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0040] Example 1
[0041] Slices of natural balsa wood with a typical thickness of 2 mm in the longitudinal direction are crushed into powder to obtain sawdust powder;
[0042] Soak sawdust powder in 80 mL of hydrogen peroxide (H 2 O 2 , 30%), 80 mL phosphoric acid solution (H 3 PO 4 , ≥85.0%) and 15 g adenine (C 5 H 5 N 5 , 99%), and soaked at 60°C for 6 h. Then soaked in deionized water for 3 times to remove dissolved chemicals, including excess H 3 PO 4 and adenine to give cellulose;
[0043] The graphene oxide aqueous solution (1 mg / m) was uniformly mixed with cellulose, pre-cooled in liquid nitrogen, and freeze-dried (-50°C, 2Pa, 6h) to obtain a modified hybrid aerogel; wherein the mass ratio of graphene oxide to cellulose was 1:10; the composite aerogel was heated to 400°C at a heating rate of 3°C / min and kept warm for 1h, and then the sample was heated to 800°C at 5°C / min and kept warm for 1h for carbonization to obtain a porous composite material based on graphene oxide and plant powder.
[0044] Example 2
[0045] Slice natural balsa wood with a typical thickness of 3 mm in the longitudinal direction and crush it into powder to obtain sawdust powder;
[0046] Soak sawdust powder in 100 mL of hydrogen peroxide (H 2 O 2 , 30%), 100 mL phosphoric acid solution (H 3 PO 4 , ≥85.0%) and 20 g adenine (C 5 H 5 N 5 , 99%), and immersed in a mixed solution at 80°C for 8 h; then immersed in deionized water for 4 times to remove dissolved chemicals, including excess H 3 PO 4 and adenine to give cellulose;
[0047] After the graphene oxide aqueous solution (2 mg / mL) was uniformly mixed with cellulose, it was pre-cooled in liquid nitrogen and freeze-dried (-60°C, 2 Pa, 8 h) to obtain the modified composite aerogel. Among them, the mass ratio of graphene oxide to cellulose was 2:10;
[0048] The composite aerogel was heated to 500°C at a heating rate of 3°C / min and kept at this temperature for 2 h. Then the sample was heated to 900°C at a heating rate of 5°C / min and kept at this temperature for 2 h for carbonization to obtain a porous composite material based on graphene oxide and plant powder.
[0049] Example 3
[0050] Slices of natural balsa wood with a typical thickness of 4 mm in the longitudinal direction are crushed into powder to obtain sawdust powder;
[0051] Soak sawdust powder in 120 mL of hydrogen peroxide (H 2 O 2 , 30%), 120 mL phosphoric acid solution (H 3 PO 4 , ≥85.0%) and 30 g adenine (C 5 H 5 N 5 , 99%) mixed solution at 100°C for 10 h. Then soak in deionized water for 5 times to remove dissolved chemicals, including excess H 3 PO 4 and adenine to give cellulose;
[0052] After the graphene oxide aqueous solution (3 mg / mL) was uniformly mixed with cellulose, it was precooled in liquid nitrogen and freeze-dried (-70°C, 2 Pa, 10 h) to obtain the modified composite aerogel. Among them, the mass ratio of graphene oxide to cellulose was 3:10;
[0053] The composite aerogel was heated to 600°C at a heating rate of 3°C / min and kept warm for 3 h. Then the sample was heated to 1000°C at 5°C / min and kept warm for 3 h for carbonization to obtain a porous composite material based on graphene oxide and plant powder.
[0054] Example 4
[0055] The preparation process of the porous composite material based on graphene oxide and plant powder in this Example 4 refers to Example 1, except that the mass ratio of graphene oxide to cellulose is 4:10.
[0056] Example 5
[0057] The preparation process of the porous composite material based on graphene oxide and plant powder in this Example 5 refers to Example 1, except that the mass ratio of graphene oxide to cellulose is 5:10.
[0058] Example 6
[0059] The preparation process of the porous composite material based on graphene oxide and plant powder in this Example 6 refers to Example 1, except that the mass ratio of graphene oxide to cellulose is 6:10.
[0060] Comparative Example 1
[0061] The preparation process of the porous composite material based on graphene oxide and plant powder in this comparative example 1 refers to that of Example 1, except that: graphene oxide is not added.
[0062] Table 1 shows the properties of the prepared porous composite materials
[0063]
[0064] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the examples without departing from the principles and spirit of the invention, the scope of the invention being defined by the appended claims and their equivalents.
Claims
1. A porous composite material based on graphene oxide and porous plant powder for use in tobacco filters, characterized in that: The porous composite material based on graphene oxide and porous plant powder is composed of neatly arranged fine pore walls, and the gaps between adjacent pores are a multi-channel structure with continuous guidance; the average pore size of the porous composite material based on graphene oxide and porous plant powder is 300 nm to 700 nm μm; the hydrophilic angle of the porous composite material based on graphene oxide and porous plant powder is 8 to 40°; The method for preparing the porous composite material based on graphene oxide and porous plant powder comprises: (1) Select porous natural balsa wood sawdust powder and soak it in a hydrogen peroxide / phosphoric acid mixed solution containing adenine, then wash and dry it to obtain cellulose; wherein the hydrogen peroxide / phosphoric acid mixed solution containing adenine comprises: 50-150 mL of a hydrogen peroxide solution with a concentration of 30 wt%, 80-150 mL of a phosphoric acid solution with a concentration of ≥85.0 wt%, and 15 g-25 g of adenine, the three being mixed to obtain the cellulose; (2) mixing the graphene oxide aqueous solution and cellulose, and obtaining a composite aerogel by pre-freezing and vacuum freeze-drying; (3) The obtained composite aerogel is carbonized at high temperature to obtain a porous composite material based on graphene oxide and porous plant powder.
2. The porous composite material based on graphene oxide and porous plant powder for tobacco filter according to claim 1, characterized in that: The particle size of the porous natural balsa wood sawdust powder is ≤6mm; porous natural balsa wood slices with a longitudinal thickness of ≤3mm are crushed to obtain porous natural balsa wood sawdust powder; the material of the porous natural balsa wood sawdust powder is at least one of balsa wood, arbor, catalpa and paulownia.
3. The porous composite material based on graphene oxide and porous plant powder for tobacco filter according to claim 1, characterized in that: The soaking treatment is performed at a temperature of 60 to 100° C. for 6 to 10 hours; the cleaning is performed by soaking in deionized water for several times to remove dissolved chemicals; the drying is performed at a temperature of 60 to 120° C. for 6 to 12 hours.
4. The porous composite material based on graphene oxide and porous plant powder for tobacco filter according to claim 1, characterized in that: The mass ratio of the cellulose to graphene oxide is 10:(1-6).
5. The porous composite material based on graphene oxide and porous plant powder for tobacco filter according to claim 1, characterized in that: The pre-freezing is to freeze and crystallize the mixed solution to a solid state.
6. The porous composite material based on graphene oxide and porous plant powder for tobacco filter according to claim 5, characterized in that: The pre-freezing temperature is ≤-10°C, and the pre-freezing time is ≥3 hours.
7. The porous composite material based on graphene oxide and porous plant powder for tobacco filter according to claim 1, characterized in that: The vacuum freeze drying is carried out at a temperature of -60 to -80°C, for a time of 6 to 10 hours, and at a vacuum degree of 1 to 10 Pa.
8. The porous composite material based on graphene oxide and porous plant powder for tobacco filter according to claim 1, characterized in that: The high temperature carbonization is as follows: firstly heating to 400-600°C and keeping the temperature for 1-3 hours, then heating to 800-1000°C and keeping the temperature for 1-3 hours; the atmosphere of the high temperature carbonization is an inert atmosphere.
9. The porous composite material based on graphene oxide and porous plant powder for tobacco filter according to any one of claims 1 to 8, characterized in that: The specific surface area of the porous composite material based on graphene oxide and porous plant powder is 60 to 550 m 2 / g .
10. The porous composite material based on graphene oxide and porous plant powder for tobacco filter according to claim 9, characterized in that: The specific surface area of the porous composite material based on graphene oxide and porous plant powder is 400-450 m 2 g -1 ; The porous composite material based on graphene oxide and porous plant powder can rebound to its original shape after being compressed to 20-80% of its volume.
Citation Information
Patent Citations
Preparation method and application of cellulose / graphene oxide carbon aerogel
CN109019597A
Preparation method of phosphoric acid activated eucalyptus charcoal adsorbent and application thereof in adsorbing Cr (VI) in water
CN112619606A